Contributing factors for sex preference among multipara mother attending Gynae OPD of Alka Hospital Pvt Ltd, Jawalakhel, Lalitpur. - Subedi, Bedh Kumari (2013)
ABSTRACT: An exploratory study to find out" Contributing factors for sex preference among multipara mother." This study was carried out in Alka Hospital of Jawalakhel among fifty participants using non probability purposive sampling techniques. Structured questionnaire was used to collect the information. Main findings of the study was 44% of participants preferred son and the contributing factors for sex preference were 48.5% in social, 28.78% in economic, 12.12% in cultural and 10.60% in religious. This study data concluded that preference for sex might increase maternal morbidity and mortality, decrease care in baby, less productivity and increased in abortion rate in future. So, therefore the researcher recommends to emphasis on female education and proper counseling service to the female for used of the family planning methods to reduce the contributing factors of sex practice.